Innovative Agricultural SME Finance Models - Global Partnership for Financial Inclusion (International Finance Corporation, Washington, DC, 2015)
This report is organized into three main sections. Section one sets out the context by describing the particular challenges and opportunities related to financing agriculture, followed by defining the target group of agricultural SME s. Section two describes a set of innovative financing models. Section three then provides a framework for an indicative assessment of these models by gathering and forming observations from the case studies. The model observations are then highlighted in three types of country contexts in which bankers in developing countries may find themselves. Preliminary assessment results are presented. The report concludes with key lessons learned on innovative agricultural financing, relevant case studies, and an outlook on further work in this area. Annexes present methodologies and case studies representing the various models.